Customer Satisfaction Mediates the Effect of Content Marketing and Product Quality on Repurchase Intention at Warunk Upnormal Bali - Dharma, I Nengah Surya Budhi; Pidada, Ida Ayu Iswari (LPPM Institut Pendidikan Nusantara Global, 2025)
The rapid decline of Warunk Upnormal, a previously successful Indonesian culinary brand that experienced a 90.7% reduction in outlets from 2020 to 2025, necessitates investigation into factors influencing repurchase intention among consumers. Despite extensive research on content marketing and product quality, the empirical literature reveals inconsistent findings regarding their direct effects on repurchase intention, suggesting potential mediating mechanisms. This quantitative study examined whether customer satisfaction mediates the relationship between content marketing, product quality, and repurchase intention. The research employed purposive sampling with 108 respondents from Badung and Denpasar who had previous purchase experience at Warunk Upnormal Bali. Data were collected through online questionnaires using a 5-point Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares (PLS-SEM) version 4.0 software with 5,000 bootstrap subsamples. Results demonstrated that content marketing exerts a direct positive significant effect on repurchase intention (β = 0.229, p = 0.009), while product quality shows positive but non-significant direct effects (β = 0.186, p = 0.051). Both variables significantly influence customer satisfaction (content marketing: β = 0.425, p < 0.001; product quality: β = 0.366, p < 0.001). Customer satisfaction mediates both relationships, with indirect effects of 0.138 (p = 0.016) for content marketing and 0.119 (p = 0.025) for product quality on repurchase intention. The overall model explains 66.8% of variance in endogenous variables. Findings reconcile previous inconsistencies by demonstrating that content marketing and product quality influence repurchase intention partially through customer satisfaction, offering managerial implications for organizational recovery and competitive repositioning in Indonesia's culinary sector.